PENGELOLAAN BUKU ADMINISTRASI DESA DI DESA SUNGAI SIPAI KECAMATAN MARTAPURA KABUPATEN BANJAR - jumarianta jumarianta (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2018)
The aim of this research is to find out how the Management of Village Administration Books in the Sipai River Pambakal Office Sungai Sipai Village, Martapura District, Banjar Regency.This study uses a qualitative descriptive method, the data digger is in the form of interviews for primary data, and observation and documentation for secondary data. Based on the results of the analysis and discussion in the previous chapter, the researchers concluded that the Village Government consisted of Village heads and other Village Tools, namely Secretary, Treasurer, Head of Government Affairs, Head of Development Affairs, Head of General Affairs, and Head of RT, according to local village conditions. . In the management of village administration there are several models of village administration books, namely, general administration books, population administration books, financial administration books, development administration books, administration books for village consultative bodies, and other administrative books. The books are already filled in completely, but some are not complete. To further optimize the technical and performance of the Village Administration Book Management, it is recommended to further improve the capacity of the village apparatus and the technical management of the administration book through training and workshops so that the management of the village administration book is getting better.